Diagnostic work-up and laparoscopic correction of an ectopic ureter. Issue 5 (October 2015) - Cezarino, B.N.; Lopes, R.I.; Oliveira, L.M.; Dénes, F.T.; Srougi, M.
Summary: Introduction: A duplex renal collecting system is a common congenital anomaly in children. Continuous dribbling (especially if after the toilet-training period) should raise suspicion of the presence of an ectopic ureter, which is most often associated with ureteral duplication. This video will demonstrate the complete diagnostic work-up necessary in these cases. Case report: A 10-year-old girl presented with continuous dribbling. Ultrasonography and computerized tomography depicted a duplex system on the left side, with the upper pole ureter ectopically inserting into the vaginal cavity and good upper pole renal parenchyma. A careful urethrocystoscopy showed a topic right ureteral orifice and a topic lower pole left ureteral orifice. Retrograde pyelography was performed and displayed normal left lower pole anatomy. A vaginography was performed, which showed reflux to the ectopic ureter. Vaginoscopy clearly identified the ectopic ureteral orifice. A guide wire was introduced through this meatus and retrograde contrast injection confirmed the diagnosis of an ectopic ureter. Results: At laparoscopy, a larger upper pole ureter and a normal lower pole ureter on the left side were identified. A termino-lateral ureteroureteral anastomosis was performed. After the procedure, the child reported immediate resolution of urinary dribbling. Conclusion: In order to optimize its surgical correction, efforts should be made to appropriate localization of the ectopic ureter.